Primary health care the role of the nurse - M. Mellish (AOSIS, 1984)
Primary Health Care, as the words imply, is the initial, or first level of health care given to individuals needing or seeking that care. The whole population needs primary health care, for it is basic to attaining, retaining or regaining health, or making the best use of what health is left.